Highly Stable and Efficient Hybrid Quantum Dot Light-Emitting Diodes - Shun-Chieh Hsu; Yin-Han Chen; Zong-Yi Tu; Hau-Vei Han; Shih-Li Lin; Teng-Ming Chen; Hao-Chung Kuo; Chien-Chung Lin (IEEE Photonics Journal)
A highly efficient and reliable hybrid quantum dot (QD) light-emitting diode (LED) is demonstrated and analyzed. The CdTe colloidal QDs are embedded in the sodium chloride (NaCl) ionic crystal to prevent external wear. The GaN-based ultraviolet (UV) LED is used as the excitation source. The mixture of colloidal QD/NaCl composite and polymer can be filled inside the standard LED package and optically pumped by the UV LED. Two different filling layer designs are fabricated simultaneously for comparative study. Due to extra scattering brought by the sodium chloride grains, the resultant photon conversion efficiency (PCE) can be as high as 72.6% at the medium current level. For the long-term stability assessment, two different UV pumping intensities were set up: One is equivalent to 111 mW/cm 2, and the other is 906 mW/cm 2. With this encapsulation, the stability of the colloidal QD light output over time can be improved, and a prolonged lifetime of 6488 h can be demonstrated under the continuous UV aging condition.